CAUSES AND OUTCOMES OF PATIENTS ADMITTED TO THE INTENSIVE CARE UNIT WITH SYSTEMIC LUPUS ERYTHEMATOSUS: Systemic Lupus Erythematosus
Objective: To identify the causes and outcome of patients admitted with systemic lupus erythmatosus (SLE) requiring intensive care unit care in a tertiary care hospital. Study Design: Retrospective record review study. Place of Duration of Study: Aga Khan University Hospital, 15 years from Jan 2001 to Dec 2015. Material and Methods: Medical record of past fifteen years (from 2001 till December 2015) was reviewed for all adult patients (age .16) admitted to intensive care unit with SLE. At the time of ICU admission patients were evaluated for demographics characteristics, clinical and laboratory parameters, length of ICU stay, Acute Physiology and Chronic Health Evaluation II (APACHE II) score and mortality. Results: During the study period, 58 patients were admitted to ICU; 47 (81%) were females and 11 (19%) were males. Out of them 42 (72%) patients died, predominantly with septic shock. The mean age was 36.1